Modified Weaver-Dunn procedure, a novel approach to type-3 acromioclavicular joint dislocation - Goud, Veer Abhishek; G., Venu; Prakash P., Surya (International Journal of Research in Orthopaedics, 2023)
Even though a generally accepted opinion is present about conservative management for type 1 and type 2 acromioclavicular dislocation and surgical management for type 4 to type 6 dislocations, different opinions come under play for conservative versus surgical management in cases with acute type 3 acromioclavicular joint dislocation. We came across 20 cases of type 3 AC joint dislocation with a varied age profile (range 18 to 50 years, mean 34.4±6.5 years). Patients usually complain of pain and swelling and difficulty in moving shoulder joint. The diagnosis can be confirmed by radiographs which shows widening of AC joint >2-4 mm and coracoclavicular distance >5 mm and superior displacement of distal clavicle. In our series, we have treated them with modified Weaver Dunn technique. Immobilized arm in arm pouch for 3 weeks and follow up was done to assess functional outcome. In this study we present the outcome and related complications with modified Weaver Dunn technique for type 3 acromioclavicular joint dislocation.